Effect of online political incivility on partisan attitude: role of issue involvement, moral identity and incivility accountability. Issue 7 (13th October 2020) - Sharma, Isha; Jain, Kokil; Singh, Gurinder
Abstract : Purpose: The study investigates the effect of an uncivil comment made by a party representative on social media and tests whether it can lead to a change in observers' attitude toward the party. Design/methodology/approach: Data are collected from 196 respondents using a scenario-based survey. Proposed model is tested using partial least square structural equation modeling (PLS-SEM). Findings: It is found that individual's moral identity and issue involvement influence perceived civility of the online post, which in turn affects attitude toward the party as well as the individual. It is observed that for high partisans, effect of perceived civility on attitude toward the party is stronger compared to low partisans. Party's lack of responsiveness to address the uncivil comment from its representative increases party's incivility accountability and lowers the partisan attitude toward the party. Originality/value: The study presents a novel understanding of how political party representatives can influence the image of the party by engaging in an uncivil discourse on social media. Results support that strong partisan would react more unfavorably indicating that loyalty toward the party cannot be taken for granted. Peer review: The peer review history for this article is available at: https://publons.com/publon/10.1108/OIR-03-2020-0084